Exposure of Pregnant Mice to Perfluorobutanesulfonate Causes Hypothyroxinemia and Developmental Abnormalities in Female Offspring. (1st November 2016) - Feng, Xuejiao; Cao, Xinyuan; Zhao, Shasha; Wang, Xiaoli; Hua, Xu; Chen, Lin; Chen, Ling
Abstract : Perfluorobutanesulfonate (PFBS) is widely used in many industrial products. We evaluated the influence of prenatal PFBS exposure on perinatal growth and development, pubertal onset, and reproductive and thyroid endocrine system in female mice. Here, we show that when PFBS (200 and 500 mg/kg/day) was orally administered to pregnant mice (PFBS-dams) on days 1–20 of gestation; their female offspring (PFBS-offspring) exhibited decreased perinatal body weight and delayed eye opening compared with control offspring. Vaginal opening and first estrus were also significantly delayed in PFBS-offspring, and diestrus was prolonged. Ovarian and uterine size, as well as follicle and corpus luteum numbers, were reduced in adult PFBS-offspring. Furthermore, pubertal and adult PFBS-offspring exhibited decreases in serum estrogen (E2) and progesterone (P4) levels with the elevation of luteinizing hormone levels. Notably, decreases in serum total thyroxine (T4) and 3, 3′, 5-triiodothyronine (T3) levels were observed in fetal, pubertal, and adult PFBS-offspring in conjunction with slight increases in thyroid-stimulating hormone (TSH) and thyrotropin-releasing hormone levels. In addition, PFBS-dams exhibited significant decreases in total T4 and T3 levels and free T4 levels and increases in TSH levels, but no changes in E2 and P4 levels. These results indicate that prenatal PFBS exposure (≥200 mg/kg/day) causes permanent hypothyroxinemia accompanied by deficits in perinatal growth, pubertal onset, and reproductive organ development in female mice.